Vocational Virtue Ethics: Prospects for a Virtue Ethic Approach to Business - McPherson, David (Journal of business ethics, 2013)
In this essay, I explore the prospects for a virtue ethic approach to business. First, I delineate two fundamental criteria that I believe must be met for any such approach to be viable: viz., the virtues must be exercised for the sake of the good of one’s life as a unitary whole (contra role-morality approaches) and for the common good of the communities of which one is a part as well as the individual good of their members (contra egoist approaches). Second, I argue that these two criteria can be met only if we are able to reconceive and transform the nature of work within contemporary business organizations. In particular, what is needed, I argue, is a retrieval of something like the older ideal of work as a “vocation”, or “calling”, whereby work can be viewed as a specific aspect of a more general calling to pursue, through the practice of the virtues, “the good life” both for ourselves and for others. Lastly, I consider some important challenges to this “vocational virtue ethic” approach to work within contemporary business organizations and offer a few suggestions for how they might be met.